Development a New Intelligent System for Monitoring Environment Information using Wireless Sensor Networks - Dener, Murat (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Wireless Sensor Networks are a new technology that has been on the agenda lately and can be applied to many areas. By using Wireless Sensor Networks, information can be gathered interactively and this information can be collectively evaluated and can be changed on the basis of information when necessary. In this work, a sensor node and a gateway node are designed and developed. With designed new nodes, a new intelligent system is developed. In the new system, Temperature, humidity, sound and water level data are perceived and monitored. This system can be used in all environments that need these four information. It is estimated that our work will benefit sensor network users.Â